Antibacterial material for cookware and preparation method of antibacterial material

By using surface-modified boron nitride nanotubes to coat silver filler and silica-loaded titanium dioxide particles in pot materials, the shortcomings of pot materials in bacteriostatic and wear resistance are solved, and efficient Antibacterial and wear-resistant effects extend the service life of the pot.

CN119463595AActive Publication Date: 2025-02-18ZHEJIANG BAHE KITCHENWARE CO LTD

Patent Information

Application Number
CN202510068003.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-02-18
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The existing pot materials have shortcomings in antibacterial and wear resistance, especially in high temperature and complex environments, which are difficult to maintain long-term antibacterial and high wear resistance.

Method used

Surface-modified boron nitride nanotubes are used to coat silver fillers and doped titanium dioxide particles with silica loading. The antibacterial and wear resistance of the coating is improved by coating silver ions and loading of silica.

Benefits of technology

It significantly improves the long-term antibacterial properties and wear resistance of the pot coating, extends the service life of the pot, and improves its stability and safety in high temperature and complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463595A_ABST
    Figure CN119463595A_ABST
Patent Text Reader

Abstract

The invention relates to the field of pot materials, and provides a pot antibacterial material and a preparation method thereof.The pot antibacterial material comprises surface modified boron nitride nanotube coated silver filler, silicon dioxide loaded doped titanium dioxide particles, polytetrafluoroethylene, organic silicon resin, a heat stabilizer, polyethylene glycol 400, ethyl alcohol and a curing agent. The preparation method comprises the following steps: mixing the modified boron nitride nanotube coated silver filler and silicon dioxide loaded doped titanium dioxide particles with polyethylene glycol 400 and ethanol, stirring, adding polytetrafluoroethylene, organic silicon resin and a heat stabilizer to prepare coating slurry, adding a curing agent, uniformly stirring, coating on the surface of a cookware base material, and curing at high temperature to form the coating. The material adopts silver doping, silicon dioxide loading and other processes, and shows excellent antibacterial property, stability and wear resistance. The invention solves the problem of insufficient antibacterial property of the cookware coating, and is suitable for the coating application of kitchen cookware.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of cookware materials, and in particular to an antibacterial material for cookware and a preparation method thereof. Background Art

[0002] With the continuous improvement of the quality of life in modern families, the functionality and safety of kitchen cookware have become the focus of consumers. As an important tool for food processing, cookware is susceptible to microbial invasion such as bacteria and mold during long-term use, especially in complex use environments such as high humidity and high temperature fume. Bacterial growth may lead to cross contamination, threatening food safety and human health. Therefore, the development of cookware materials with high-efficiency antibacterial properties has become a key demand in the cookware industry. At the same time, cookware needs to withstand frequent friction, scratching and high temperature conditions during use, which puts higher requirements on the wear resistance of its surface coating. Cookware materials not only need to maintain long-term antibacterial properties in extreme environments, but also need to have excellent wear resistance to ensure their service life and stability. Therefore, cookware coating materials that meet the dual requirements of antibacterial and wear resistance can not only significantly improve the hygiene and safety of cookware, but also extend its service life and reduce replacement costs, which is of great significance to improving consumer experience and promoting industry technology upgrades. The continuous optimization and breakthrough of material performance will provide the cookware industry with higher value-added products and further broaden its application scenarios, thereby promoting the widespread application of green, healthy and high-performance cookware.

[0003] At present, the research and development of coating materials for cookware has achieved certain results, but there are still many shortcomings. For example, the Chinese patent with patent number CN107981702B discloses an antibacterial non-stick cookware and its manufacturing method, which achieves antibacterial effect by adding silver ions to the coating, but because silver ions are easily inactivated under high temperature environment, the long-term antibacterial performance is insufficient. At the same time, the existing coating materials also have obvious limitations in wear resistance. For example, the Chinese patent with patent number CN107080468B introduces a high-hardness wear-resistant coating, but its wear resistance decreases rapidly under strong friction environment, and cannot meet the long-term use requirements of cookware. The main reasons for these shortcomings are the singleness of the material system design and the limitations of its performance balance: on the one hand, traditional antibacterial materials usually rely on the physical or chemical action of a single antibacterial agent, and it is difficult to maintain long-term antibacterial in a complex environment; on the other hand, the wear-resistant coating usually aims at high hardness, but in actual use, it lacks flexibility and scratch resistance and shows low comprehensive performance. Therefore, how to simultaneously achieve long-lasting antibacterial properties and high wear resistance in cookware materials has become a key problem in the current technical field, and is also an important direction that the cookware industry urgently needs to break through. Summary of the invention

[0004] (1) Technical issues solved The purpose of the present invention is to provide an antibacterial material for cookware and a preparation method thereof, so as to solve the problem that the current cookware materials have insufficient antibacterial and wear-resistant properties.

[0005] (2) Technical solution In order to achieve the above object, the present invention provides the following technical solutions: A cookware antibacterial material comprises the following components, measured by weight: 0.5-1.5 parts of surface-modified boron nitride nanotube-coated silver filler, 3-8 parts of silicon dioxide-loaded doped titanium dioxide particles, 25-35 parts of polytetrafluoroethylene, 10-15 parts of silicone resin, 1.0-3.0 parts of heat stabilizer, 0.5-1 parts of polyethylene glycol 400, 45-55 parts of ethanol, and 1-3 parts of curing agent.

[0006] Further, the preparation method of the surface modified boron nitride tube coated silver filler is as follows: by weight, 10 to 18 parts of boron nitride tube coated silver filler are added to 100 to 150 parts of anhydrous ethanol, stirred at a stirring rate of 500 to 700 rpm for 30 to 40 minutes, and after stirring, ultrasonic treatment is performed to obtain a suspension, wherein the parameters of the ultrasonic treatment are: sound power of 200 to 300 W, frequency of 40 to 50 kHz, and ultrasonic time of 20 to 30 minutes, and then 1.0 to 2.5 parts of KH-550 are added, and then at a temperature of 60 to 80 ° C, stirring is continued at a stirring rate of 300 to 500 rpm for 20 to 30 minutes. After stirring, the reaction solution is separated by vacuum filtration, the filter residue is collected, and the filter residue is transferred to a beaker and 100 to 150 The mixture was washed with 50 mL of anhydrous ethanol for 3 to 4 times, with each stirring time of 5 to 10 min, to remove unreacted KH-550 and impurities. After washing, the residue was filtered and placed in a vacuum drying oven, and dried at 60 to 70 ° C for 10 to 12 h to obtain a surface-modified boron nitride tube coated with silver filler.

[0007] Further, the preparation method of the boron nitride tube coated silver filler is as follows: 3.0-4.5 parts of boron nitride nanotubes are weighed in parts by weight and placed in a 250 mL beaker, 100-150 mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 500-700 rpm for 20-30 minutes, then the beaker is placed in an ultrasonic cleaner, and ultrasonically treated for 20-30 minutes under the conditions of an ultrasonic power of 200-300 W and a frequency of 40-50 kHz to form a boron nitride nanotube suspension, 1.0-1.5 parts of silver nitrate are weighed and dissolved in 100-150 mL of deionized water to obtain a silver nitrate solution, the boron nitride nanotube suspension is added to the silver nitrate solution, and the beaker is placed on a magnetic stirrer and stirred at a stirring rate of 500-700 rpm for 30-40 min, transfer the mixed solution to a vacuum ultrasonic device, and perform ultrasonic treatment under a vacuum pressure of -0.08-0.1 MPa, with an ultrasonic power of 200-300 W, a frequency of 40-50 kHz, and a treatment time of 20-30 min. After the vacuum ultrasonic treatment, return to normal pressure, heat the mixed solution to 50-60 °C, and then slowly add 0.1 mol / L glucose solution at a drop rate of 1-2 mL / min. The total volume is controlled at 20-30 mL. Continue to maintain constant temperature stirring for 60-90 min until the color of the solution gradually changes from colorless to light gray. After the reaction solution is cooled, separate it by vacuum filtration, collect the filter residue, and wash it 2-3 times with deionized water, each time with 100-150 mL, and then wash it 1-2 times with anhydrous ethanol, each time with 50-100 mL, the washed filter residue was transferred to a vacuum drying oven and dried at 60-70 °C for 10-12 h to obtain a boron nitride tube coated with silver filler.

[0008] Further, the preparation method of the boron nitride tube is as follows: 5.0-8.0 parts of amorphous boron powder are weighed by weight and placed in a graphite crucible of a high-temperature inert atmosphere tube furnace, the inside of the tube furnace is evacuated to vacuum, the vacuum degree is controlled at -0.08-0.1 MPa, and then argon is introduced for protection, the flow rate is controlled at 200-300 mL / min, the furnace temperature is heated to 800-1100°C at a heating rate of 5-10°C / min, and the temperature is kept for 30-60 min, the boron powder is activated, and after the activation treatment is completed, the furnace temperature is continued to be heated to 1200-1400°C at a heating rate of 10-20°C / min, and 200-400 mL / min of ammonia is introduced for nitridation reaction, and the insulation time is 2-4 hours. After the reaction is completed, the ammonia is stopped, and 200-300 mL / min of ammonia is introduced. mL / min of argon, the furnace temperature was lowered to room temperature at a cooling rate of 5~10℃ / min to obtain a preliminarily generated boron nitride product, the preliminarily generated product was taken out and placed in a beaker, 100~150 mL of 0.1~0.5 mol / L dilute hydrochloric acid solution was added, and the mixture was placed on a magnetic stirrer and stirred at a stirring rate of 300~500 rpm for 30~60 min, and the product was acid-washed, and the acid-washed product was washed with deionized water for 3~5 times, each time with an amount of 100~150 mL, until the pH of the washing solution was close to neutral, and then washed with anhydrous ethanol for 1~2 times, each time with an amount of 50~100 mL, to complete further washing, and the washed product was transferred to a vacuum drying oven, and dried at 60~80℃ for 12~24h to obtain dry boron nitride nanotubes.

[0009] Furthermore, the surface modified boron nitride tube coated with silver filler has an average diameter of 15-65 nm and an average length of 550-1350 nm.

[0010] The present invention adopts the design of surface-modified boron nitride nanotubes coated with silver fillers, which is mainly used to enhance the long-term antibacterial performance and wear resistance of the cookware coating. Through the surface modification of boron nitride nanotubes and the coating design of silver ions during the preparation process, the high mechanical strength and excellent thermal stability of boron nitride nanotubes are used as the matrix, combined with the broad-spectrum antibacterial properties of silver ions, the antibacterial ability of the coating material under high temperature and complex environment is effectively improved. In addition, by introducing KH-550 silane coupling agent during the coating process, the binding force between silver ions and boron nitride nanotubes is enhanced, which not only improves the dispersibility of filler particles, but also enhances the overall structural stability of the coating, thereby providing excellent antibacterial durability in long-term use. The preparation of boron nitride nanotubes adopts a high-temperature nitridation reaction process to ensure the integrity and dimensional uniformity of its one-dimensional structure, and the subsequent pickling and ultrasonic treatment further remove impurities, improve the purity and surface activity of the material, which lays a good foundation for the subsequent silver ion coating. During the silver ion coating process, through vacuum ultrasonic treatment and glucose reduction process, silver particles can be evenly distributed inside the boron nitride nanotubes to form highly effective antibacterial active centers. In addition, the high strength of the modified boron nitride nanotubes and the uniform distribution of silver particles work together to improve the material's tolerance to friction and scratches in the cookware coating, meeting the dual needs of durability and hygiene for kitchen cookware in high-frequency use scenarios. The synergy between the components fully reflects the design purpose, and the high performance of the cookware coating is achieved through the optimization of material properties.

[0011] Further, the preparation method of the silica-loaded doped titanium dioxide particles is as follows: by weight, 5.0-7.0 parts of doped titanium dioxide particles are weighed and placed in a 250 mL beaker, 100-150 mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 300-500 rpm for 30-40 min until a uniform dispersion is formed, 3.0-5.0 parts of tetraethyl orthosilicate are weighed and slowly added to the above dispersion, the dropping rate is controlled to 1.0-2.0 mL / min, while the stirring rate is maintained at 400-600 rpm, and stirring is continued for 30-60 min until the tetraethyl orthosilicate is completely mixed, and 0.1 mol / L hydrochloric acid solution is slowly added to the resulting mixed solution at a dropping rate of 0.5-1.0 mL / min, while maintaining the stirring rate at 300~500rpm, adjusting the solution pH to 2.0~4.0, and continuing to stir for 30~60min to complete the hydrolysis process of ethyl orthosilicate, transferring the resulting solution to a water bath at 80~90℃, heating and maintaining constant temperature stirring for 60~90min to promote the deposition of silicon dioxide on the surface of doped titanium dioxide particles. After the reaction is completed, the reaction solution is naturally cooled to room temperature, and the resulting precipitate is separated by vacuum filtration, the filtrate is discarded, and the precipitate is washed with deionized water 3~5 times, each time with an amount of 100~150 mL, to remove unreacted impurities and by-products, and then washed with anhydrous ethanol 1~2 times, each time with an amount of 50~100 mL, the washed precipitate is transferred to a vacuum drying oven and dried at 60-80°C for 8-12h to obtain dry silica-loaded doped titanium dioxide particles. The dried sample is placed in a tubular furnace and heated to 400-500°C at a heating rate of 3-5°C / min and kept warm in an air atmosphere for 2-4 hours. After the sintering treatment of the material is completed, silica-loaded doped titanium dioxide particles are obtained.

[0012] Further, the preparation method of the doped titanium dioxide particles is as follows: 10.0-15.0 parts of tetrabutyl titanate are weighed in parts by weight and placed in a 250 mL beaker, 50-100 mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 400-600 rpm for 30-40 min until a uniform tetrabutyl titanate solution is formed; 0.5-2.0 parts of silver nitrate are weighed and dissolved in 20-50 mL of deionized water to obtain a silver nitrate solution; the silver nitrate solution is slowly added dropwise to the tetrabutyl titanate solution at a dropping rate of 1.0-2.0 mL / min, while the stirring rate is maintained at 500-700 rpm, and the stirring is continued for 30-60 min to ensure that the silver ions are evenly dispersed in the tetrabutyl titanate solution, and 0.1 mol / L of hydrochloric acid solution is slowly added dropwise to the above-mentioned mixed solution at a dropping rate of 1.0-2.0 mL / min, and the stirring rate is maintained at 400-600 rpm. rpm, adjust the solution pH to 1.0-3.0 to promote the hydrolysis reaction of tetrabutyl titanate. After the dropwise addition is completed, the resulting solution is transferred to a reactor and heated at 80-100°C for 6-12 hours to complete the formation of titanate gel and the silver ion doping process. After the reaction is completed, the reactor is naturally cooled to room temperature. The resulting product is separated by vacuum filtration, and the filtrate is discarded. The filtered precipitate is washed with deionized water for 3-5 times, each time with an amount of 100-150 mL to remove residual impurities and unreacted silver ions, and then washed with anhydrous ethanol 1-2 times, each time with an amount of 50-100 mL to promote drying. The washed precipitate is transferred to a vacuum drying oven and dried at 60-80°C for 8-12 hours to obtain a dry silver-doped titanium dioxide precursor powder. The dried precursor powder is placed in a high-temperature tube furnace, heated to 450~550℃ at a heating rate of 3~5℃ / min, and kept warm in an air atmosphere for 2~4h. After sintering, it is naturally cooled to room temperature, and doped titanium dioxide particles are obtained after grinding and dispersion.

[0013] The present invention adopts the design of doped titanium dioxide particles loaded with silica, which is mainly used to enhance the antibacterial performance and stability of the cookware coating. By loading silica on the surface of doped titanium dioxide particles, the synergistic optimization of material properties is achieved. During the preparation process, the doped titanium dioxide particles use tetrabutyl titanate as a precursor, and silver ions are doped and the hydrolysis conditions are regulated to ensure that the silver ions are evenly distributed in the titanium dioxide particle structure, thereby giving the particles excellent antibacterial properties and chemical stability. Subsequently, during the hydrolysis of ethyl orthosilicate, silica is gradually deposited on the surface of the doped titanium dioxide particles to form a uniformly covered load layer. This design not only further improves the dispersibility and mechanical stability of the particles, but also effectively enhances the durability and corrosion resistance of the coating in a complex environment. The uniformity of the silica deposition process is promoted by adjusting the pH value of the solution with hydrochloric acid and heating in a water bath, ensuring the integrity of the material structure and the full play of the functionality. Finally, the crystal structure optimization of the material and the enhancement of the particle surface activity are achieved through a high-temperature sintering process, thereby improving the antibacterial activity and environmental adaptability. The loading of silica not only provides a physical barrier to prevent the loss of silver ions, but also improves the stability and service life of the overall material through the nano effect. The synergy between the components is fully reflected in this design. The doped titanium dioxide particles provide antibacterial active centers, and the silica loading layer enhances the mechanical properties and chemical stability of the material. These characteristics work together to significantly improve the comprehensive performance of the cookware coating, meeting the dual needs of antibacterial properties and stability in complex scenarios such as high-frequency use and high temperature and humidity.

[0014] Furthermore, the average diameter of the silica-loaded titanium dioxide doped particles is 120-250 nm.

[0015] Furthermore, the thermal stabilizer is Irganox 1010 or benzotriazole.

[0016] Furthermore, the curing agent is triethylenetetramine or di-tert-butyl peroxide.

[0017] The present invention also provides a method for preparing an antibacterial material for a cookware, comprising the following steps: S1. Place surface-modified boron nitride nanotubes coated with silver filler and silica-loaded doped titanium dioxide particles and polyethylene glycol in a 500mL beaker, add half of ethanol, place the beaker on a magnetic stirrer, and stir at a stirring rate of 500-700rpm for 30-60min until a uniform nanomaterial dispersion is formed, add polytetrafluoroethylene powder, silicone resin and thermal stabilizer to the above nanomaterial dispersion, continue stirring at a rate of 400-600rpm, gradually add the remaining other half of ethanol, and stir for 60-90min to ensure that the polytetrafluoroethylene and silicone resin are fully mixed and evenly dispersed to obtain a uniform mixed solution.

[0018] S2. Heat the uniform mixed liquid obtained in step S1 to 50-60°C, increase the temperature at a heating rate of 2-5°C / min, and maintain constant temperature stirring for 60-90 minutes to promote solvent volatilization and form a high-viscosity coating slurry. After the slurry is formed, slowly add the curing agent and continue stirring at a stirring rate of 400-600rpm for 30-60 minutes to ensure that the curing agent and the slurry are fully mixed.

[0019] S3. Apply the obtained slurry on the clean and dry surface of the cookware substrate by spraying or scraping. The coating thickness is controlled at 20~50μm. After coating, place the cookware in an oven at 60~80℃ and keep it warm for 30~60min to preliminarily dry the coating. Then transfer the cookware to a high-temperature oven and heat it to 250~300℃ at a heating rate of 5~10℃ / min and keep it warm for 2~4h to complete the curing and adhesion process of the coating. After curing, naturally cool the cookware to room temperature to finally obtain an antibacterial material for cookware.

[0020] (3) Beneficial technical effects 1. The present invention is significantly superior to the existing technology in improving the long-term antibacterial and wear resistance of cookware coatings through the innovative design of surface-modified boron nitride nanotubes coated with silver fillers. The high strength and thermal stability of boron nitride nanotubes synergize with the antibacterial properties of silver ions, combined with the KH-550 silane coupling agent to enhance the binding force, thereby achieving the durability of the antibacterial performance and the stability of the coating structure. The optimized preparation process ensures the purity and dispersibility of the material, so that the silver particles are evenly distributed to form a highly efficient antibacterial active center. The various components synergistically improve the comprehensive performance of the coating in high temperature and frequent friction environments, significantly extend the service life of cookware, meet the needs of high-frequency usage scenarios, and promote the industry progress of antibacterial and wear-resistant coating technology.

[0021] 2. The present invention significantly improves the antibacterial performance and stability of the cookware coating through the design of doped titanium dioxide particles loaded with silica, which is superior to the existing technology. Doped titanium dioxide particles provide efficient antibacterial active centers, the uniform distribution of silver ions enhances the antibacterial effect, and the silica loading layer improves the mechanical properties and chemical stability through physical barriers and nano effects. The synergistic effect of each component ensures the durability and safety of the coating in high temperature, humidity and frequent use scenarios, which promotes the industry development of durable antibacterial coating technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a transmission electron microscope morphology image of the surface-modified boron nitride nanotube-coated silver filler prepared in Example 1 of the present invention;

[0023] Figure 2 This is a scanning electron microscope morphology image of the doped titanium dioxide particles prepared in Example 1 of the present invention;

[0024] Figure 3 This is a scanning electron microscope morphology image of the silica-doped titanium dioxide particles prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0026] Example 1

[0027] An antibacterial material for cookware and a preparation method thereof, comprising the following components, measured in parts by weight: 0.5 parts of surface-modified boron nitride nanotube-coated silver filler, 3 parts of doped titanium dioxide particles loaded with silicon dioxide, 25 parts of polytetrafluoroethylene, 10 parts of organic silicone resin, 1.0 part of a thermal stabilizer, 0.5 parts of polyethylene glycol 400, 45 parts of ethanol, and 1 part of a curing agent.

[0028] The preparation method of the surface modified boron nitride tube coated silver filler of this embodiment is as follows: by weight, 10 parts of boron nitride tube coated silver filler are added to 100 parts of anhydrous ethanol, stirred at a stirring rate of 500 rpm for 30 minutes, and after the stirring is completed, ultrasonic treatment is performed to obtain a suspension, wherein the parameters of the ultrasonic treatment are: sound power of 200 W, frequency of 40 kHz, and ultrasonic time of 20 minutes, then 1.0 part of KH-550 is continued to be added, and then at a temperature of 60°C, stirring is continued at a stirring rate of 300 rpm for 20 minutes. After the stirring is completed, the reaction solution is separated by vacuum filtration, and the filter residue is collected. The filter residue is transferred to a beaker and washed with 100 mL of anhydrous ethanol for 3 times, each stirring time is 5 minutes to remove unreacted KH-550 and impurities. After the washing is completed, the filter residue is filtered and placed in a vacuum drying oven, and dried at 60°C for 10 hours to obtain a surface modified boron nitride tube coated silver filler.

[0029] The preparation method of the boron nitride tube coated silver filler of the present embodiment is as follows: 3.0 parts of boron nitride nanotubes are weighed in parts by weight and placed in a 250 mL beaker, 100 mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 500 rpm for 20 min, then the beaker is placed in an ultrasonic cleaner, and ultrasonic treatment is performed for 20 min under the conditions of an ultrasonic power of 200 W and a frequency of 40 kHz to form a boron nitride nanotube suspension, 1.0 parts of silver nitrate is weighed and dissolved in 100 mL of deionized water to obtain a silver nitrate solution, the boron nitride nanotube suspension is added to the silver nitrate solution, the mixture is placed on a magnetic stirrer, and stirred at a stirring rate of 500 rpm for 30 min, the mixed solution is transferred to a vacuum ultrasonic device, and heated at -0.0 Ultrasonic treatment was carried out under vacuum pressure of 8MPa, with an ultrasonic power of 200W, a frequency of 40kHz, and a treatment time of 20min. After the vacuum ultrasonic treatment, the mixture was restored to normal pressure, and the mixed solution was heated to 50°C. Subsequently, 0.1mol / L glucose solution was slowly added dropwise at a rate of 1mL / min. The total volume was controlled at 20mL, and constant temperature stirring was continued for 60min until the color of the solution gradually changed from colorless to light gray. The reaction solution was cooled and separated by vacuum filtration, the filter residue was collected, and washed twice with deionized water, each time with an amount of 100mL, and then washed once with anhydrous ethanol, each time with an amount of 50mL. The washed filter residue was transferred to a vacuum drying oven and dried at 60°C for 10h to obtain a boron nitride tube coated with silver filler.

[0030] The preparation method of the boron nitride tube of the present embodiment is as follows: 5.0 parts of amorphous boron powder are weighed by weight and placed in a graphite crucible of a high-temperature inert atmosphere tube furnace, the inside of the tube furnace is evacuated to a vacuum, the vacuum degree is controlled at -0.08MPa, and then argon gas is introduced for protection, the flow rate is controlled at 200mL / min, the furnace temperature is heated to 800°C at a heating rate of 5°C / min, and the temperature is kept for 30min to activate the boron powder. After the activation treatment is completed, the furnace temperature is continued to be heated to 1200°C at a heating rate of 10°C / min, and 200mL / min of ammonia is introduced for nitridation reaction at the same time, and the insulation time is 2h. After the reaction is completed, the introduction of ammonia is stopped, and 200mL / min of argon is introduced. mL / min of argon, the furnace temperature was lowered to room temperature at a cooling rate of 5°C / min to obtain a preliminarily generated boron nitride product, the preliminarily generated product was taken out and placed in a beaker, 100mL of 0.1mol / L dilute hydrochloric acid solution was added, placed on a magnetic stirrer, and stirred at a stirring rate of 300rpm for 30min, the product was acid-washed, and the product after acid washing was washed with deionized water for 3 times, each time with an amount of 100mL, until the pH of the washing solution was close to neutral, and then washed once with anhydrous ethanol, each time with an amount of 50mL, to complete further washing, and the washed product was transferred to a vacuum drying oven and dried at 60°C for 12h to obtain dry boron nitride nanotubes.

[0031] The surface-modified boron nitride tube coated with silver filler in this embodiment has an average diameter of 15 nm and an average length of 550 nm.

[0032] The preparation method of the silica-loaded doped titanium dioxide particles of this embodiment is as follows: by weight, 5.0 parts of doped titanium dioxide particles are weighed and placed in a 250 mL beaker, 100 mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 300 rpm for 30 min until a uniform dispersion is formed, 3.0 parts of tetraethyl orthosilicate are weighed and slowly added to the above dispersion, the dropping rate is controlled to 1.0 mL / min, and the stirring rate is maintained at 400 rpm, and stirring is continued for 30 min until the tetraethyl orthosilicate is completely mixed, 0.1 mol / L hydrochloric acid solution is slowly added to the resulting mixed solution, the dropping rate is controlled to 0.5 mL / min, and the stirring rate is maintained at 300 rpm, the pH of the solution is adjusted to 2.0, and stirring is continued for 30 min to complete the water addition of tetraethyl orthosilicate. The solution was transferred to a water bath at 80°C, heated and kept at constant temperature for 60 minutes to promote the deposition of silica on the surface of the doped titanium dioxide particles. After the reaction was completed, the reaction solution was naturally cooled to room temperature, and the obtained precipitate was separated by vacuum filtration. The filtrate was discarded, and the precipitate was washed with deionized water for 3 times, each time with an amount of 100 mL, to remove unreacted impurities and by-products, and then washed with anhydrous ethanol once, each time with an amount of 50 mL. The washed precipitate was transferred to a vacuum drying oven and dried at 60°C for 8 hours to obtain dry silica-loaded doped titanium dioxide particles. The dried sample was placed in a tubular furnace, heated to 400°C at a heating rate of 3°C / min, and kept warm in an air atmosphere for 2 hours. After the sintering treatment of the material, silica-loaded doped titanium dioxide particles were obtained.

[0033] The preparation method of the doped titanium dioxide particles of this embodiment is as follows: 10.0 parts of tetrabutyl titanate are weighed by weight and placed in a 250mL beaker, 50mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 400rpm for 30min until a uniform tetrabutyl titanate solution is formed; 0.5 parts of silver nitrate are weighed and dissolved in 20mL of deionized water to obtain a silver nitrate solution; the silver nitrate solution is slowly added dropwise to the tetrabutyl titanate solution at a dropping rate of 1.0mL / min, while the stirring rate is maintained at 500rpm, and stirring is continued for 30min to ensure that the silver ions are uniformly dispersed in the tetrabutyl titanate solution, and 0.1mol / L of hydrochloric acid solution is slowly added dropwise to the above-mentioned mixed solution at a dropping rate of 1.0mL / min, and the stirring rate is maintained at 400rpm, and the pH of the solution is adjusted to 1.0 to promote the formation of tetrabutyl titanate. A hydrolysis reaction was carried out. After the addition was completed, the obtained solution was transferred to a reactor and heated at 80°C for 6 hours to complete the formation of titanate gel and the silver ion doping process. After the reaction was completed, the reactor was naturally cooled to room temperature. The obtained product was separated by vacuum filtration, and the filtrate was discarded. The filtered precipitate was washed with deionized water for 3 times, each time with an amount of 100 mL to remove residual impurities and unreacted silver ions, and then washed with anhydrous ethanol once, each time with an amount of 50 mL to promote drying. The washed precipitate was transferred to a vacuum drying oven and dried at 60°C for 8 hours to obtain a dry silver-doped titanium dioxide precursor powder. The dried precursor powder was placed in a high-temperature tube furnace, heated to 450°C at a heating rate of 3°C / min, and kept in an air atmosphere for 2 hours. After sintering was completed, it was naturally cooled to room temperature, and doped titanium dioxide particles were obtained after grinding and dispersion.

[0034] The average diameter of the silica-loaded doped titanium dioxide particles of this example is 120 nm.

[0035] The heat stabilizer in this embodiment is Irganox 1010.

[0036] The curing agent in this embodiment is di-tert-butyl peroxide.

[0037] A method for preparing an antibacterial material for cookware according to this embodiment includes the following steps: S1. Place the surface-modified boron nitride nanotubes coated with silver filler and silica-loaded doped titanium dioxide particles and polyethylene glycol in a 500mL beaker, add half of ethanol, place the beaker on a magnetic stirrer, and stir at a stirring rate of 500rpm for 30min until a uniform nanomaterial dispersion is formed, add polytetrafluoroethylene powder, silicone resin and thermal stabilizer to the above nanomaterial dispersion, continue stirring at a rate of 400rpm, and gradually add the remaining other half of ethanol for 60min to ensure that the polytetrafluoroethylene and silicone resin are fully mixed and evenly dispersed to obtain a uniform mixed solution.

[0038] S2. Heat the uniform mixed liquid obtained in step S1 to 50°C, increase the temperature at a heating rate of 2°C / min, and maintain constant temperature stirring for 60 minutes to promote solvent volatilization and form a high-viscosity coating slurry. After the slurry is formed, slowly add the curing agent and continue stirring at a stirring rate of 400 rpm for 30 minutes to ensure that the curing agent and the slurry are fully mixed.

[0039] S3. Coat the obtained slurry on the surface of the clean and dry cookware substrate by scraping, and control the coating thickness to 20μm. After coating, place the cookware in an oven at 60℃ and keep it warm for 30 minutes to preliminarily dry the coating. Then transfer the cookware to a high-temperature oven, heat it to 250℃ at a heating rate of 5℃ / min, and keep it warm for 2h to complete the curing and adhesion process of the coating. After curing, naturally cool the cookware to room temperature to finally obtain an antibacterial material for cookware.

[0040] This study verified the structure and properties of the material prepared in Example 1 of the present invention through microscopic analysis. Figure 1 The transmission electron microscope morphology of the surface-modified boron nitride nanotubes coated with silver filler shows that silver is evenly coated inside the boron nitride nanotubes, proving the effectiveness of material preparation. Figure 2 The scanning electron microscope morphology image of the doped titanium dioxide particles shows that the surface of the particles is smooth, which further confirms the morphological characteristics of the prepared particles. Figure 3 The scanning electron microscope morphology of the loaded silica-doped titanium dioxide particles shows a rough surface morphology of the particles, which indicates the successful loading of silica and the significant change of the material structure. The above results fully demonstrate the effectiveness of the preparation method of the present invention and the expected construction of the material structure. Example 2

[0041] An antibacterial material for cookware and a preparation method thereof, comprising the following components, measured in parts by weight: 0.8 parts of surface-modified boron nitride nanotube-coated silver filler, 4.5 parts of doped titanium dioxide particles loaded with silicon dioxide, 28 parts of polytetrafluoroethylene, 11.5 parts of organic silicone resin, 1.6 parts of a heat stabilizer, 0.6 parts of polyethylene glycol 400, 48 parts of ethanol, and 1.6 parts of a curing agent.

[0042] The preparation method of the surface modified boron nitride tube coated silver filler of this embodiment is as follows: by weight, 12.4 parts of boron nitride tube coated silver filler are added to 115 parts of anhydrous ethanol, stirred at a stirring rate of 560 rpm for 33 minutes, and ultrasonic treatment is performed after the stirring is completed to obtain a suspension, wherein the parameters of the ultrasonic treatment are: sound power of 230 W, frequency of 43 kHz, and ultrasonic time of 23 minutes, and then 1.5 parts of KH-550 are continued to be added, and then at a temperature of 66°C, stirring is continued at a stirring rate of 360 rpm for 23 minutes. After the stirring is completed, the reaction solution is separated by vacuum filtration, and the filter residue is collected. The filter residue is transferred to a beaker and washed 3 times with 115 mL of anhydrous ethanol, each stirring time is 6.5 minutes to remove unreacted KH-550 and impurities. After the washing is completed, the filter residue is filtered and placed in a vacuum drying oven, and dried at 63°C for 10.6 hours to obtain a surface modified boron nitride tube coated silver filler.

[0043] The preparation method of the boron nitride tube coated silver filler of the present embodiment is as follows: 3.5 parts of boron nitride nanotubes are weighed by weight and placed in a 250 mL beaker, 115 mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 560 rpm for 23 minutes, then the beaker is placed in an ultrasonic cleaner, and ultrasonic treatment is performed for 23 minutes under the conditions of an ultrasonic power of 230 W and a frequency of 43 kHz to form a boron nitride nanotube suspension, 1.2 parts of silver nitrate are weighed and dissolved in 115 mL of deionized water to obtain a silver nitrate solution, the boron nitride nanotube suspension is added to the silver nitrate solution, the mixture is placed on a magnetic stirrer, and stirred at a stirring rate of 560 rpm for 33 minutes, the mixed solution is transferred to a vacuum ultrasonic device, and the mixture is heated at -0.086 M Pa under vacuum pressure conditions, with an ultrasonic power of 230 W, a frequency of 43 kHz, and a treatment time of 23 min. After the vacuum ultrasonic treatment, the mixture was restored to normal pressure, and the mixed solution was heated to 53 ° C. Then, 0.1 mol / L glucose solution was slowly added dropwise at a rate of 1.3 mL / min. The total volume was controlled at 23 mL. Constant temperature stirring was continued for 69 min until the color of the solution gradually changed from colorless to light gray. The reaction solution was cooled and separated by vacuum filtration. The filter residue was collected and washed twice with deionized water, each time with an amount of 115 mL. Subsequently, it was washed once with anhydrous ethanol, each time with an amount of 65 mL. The washed filter residue was transferred to a vacuum drying oven and dried at 63 ° C for 10.6 h to obtain a boron nitride tube coated with silver filler.

[0044] The preparation method of the boron nitride tube of the present embodiment is as follows: 5.9 parts of amorphous boron powder are weighed by weight and placed in a graphite crucible of a high-temperature inert atmosphere tube furnace, the inside of the tube furnace is evacuated to a vacuum, the vacuum degree is controlled at -0.086MPa, and then argon gas is introduced for protection, the flow rate is controlled at 230mL / min, the furnace temperature is heated to 890°C at a heating rate of 6.5°C / min, and the temperature is kept for 39min to activate the boron powder. After the activation treatment is completed, the furnace temperature is continued to be heated to 1260°C at a heating rate of 13°C / min, and 260mL / min of ammonia is introduced for nitridation reaction at the same time, and the insulation time is 2.6h. After the reaction is completed, the introduction of ammonia is stopped, and 230 mL / min of argon, the furnace temperature was lowered to room temperature at a cooling rate of 6.5℃ / min to obtain a preliminarily generated boron nitride product, the preliminarily generated product was taken out and placed in a beaker, 115mL of 0.22mol / L dilute hydrochloric acid solution was added, placed on a magnetic stirrer, and stirred at a stirring rate of 360rpm for 39min, the product was acid-washed, and the product after acid washing was washed with deionized water for 3 times, each time with an amount of 115mL, until the pH of the washing solution was close to neutral, and then washed once with anhydrous ethanol, each time with an amount of 65mL, to complete further washing, and the washed product was transferred to a vacuum drying oven and dried at 66℃ for 15.6h to obtain dry boron nitride nanotubes.

[0045] The surface-modified boron nitride tube coated with silver filler in this embodiment has an average diameter of 37 nm and an average length of 790 nm.

[0046] The preparation method of the silica-loaded doped titanium dioxide particles of this embodiment is as follows: 5.6 parts of doped titanium dioxide particles are weighed by weight and placed in a 250 mL beaker, 115 mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 360 rpm for 33 min until a uniform dispersion is formed, 3.6 parts of tetraethyl orthosilicate are weighed and slowly added to the above dispersion, the dropping rate is controlled to 1.3 mL / min, and the stirring rate is maintained at 460 rpm, and stirring is continued for 39 min until the tetraethyl orthosilicate is completely mixed, 0.1 mol / L hydrochloric acid solution is slowly added to the resulting mixed solution, the dropping rate is 0.65 mL / min, and the stirring rate is maintained at 360 rpm, the pH of the solution is adjusted to 2.6, and stirring is continued for 39 min to complete the hydrolysis process of tetraethyl orthosilicate , the resulting solution was transferred to a water bath at 83°C, heated and kept at a constant temperature for 69 minutes to promote the deposition of silica on the surface of the doped titanium dioxide particles. After the reaction was completed, the reaction solution was naturally cooled to room temperature, and the resulting precipitate was separated by vacuum filtration, the filtrate was discarded, and the precipitate was washed with deionized water three times, each time with an amount of 115 mL, to remove unreacted impurities and by-products, and then washed once with anhydrous ethanol, each time with an amount of 65 mL. The washed precipitate was transferred to a vacuum drying oven and dried at 66°C for 9.2 hours to obtain dry silica-loaded doped titanium dioxide particles. The dried sample was placed in a tubular furnace, heated to 430°C at a heating rate of 3.6°C / min, and kept warm in an air atmosphere for 2.6 hours. After completing the sintering treatment of the material, silica-loaded doped titanium dioxide particles were obtained.

[0047] The preparation method of the doped titanium dioxide particles of this embodiment is as follows: 11.5 parts of tetrabutyl titanate are weighed by weight and placed in a 250mL beaker, 65mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 460rpm for 33min until a uniform tetrabutyl titanate solution is formed; 0.95 parts of silver nitrate are weighed and dissolved in 29mL of deionized water to obtain a silver nitrate solution; the silver nitrate solution is slowly added dropwise to the tetrabutyl titanate solution at a dropping rate of 1.3mL / min, while the stirring rate is maintained at 560rpm, and stirring is continued for 39min to ensure that the silver ions are uniformly dispersed in the tetrabutyl titanate solution, and 0.1mol / L of hydrochloric acid solution is slowly added dropwise to the above-mentioned mixed solution at a dropping rate of 1.3mL / min, and the stirring rate is maintained at 460rpm, and the pH of the solution is adjusted to 1.6 to promote the hydrolysis of tetrabutyl titanate After the reaction is completed, the resulting solution is transferred to a reactor and heated at 86°C for 7.8 hours to complete the formation of titanate gel and the silver ion doping process. After the reaction is completed, the reactor is naturally cooled to room temperature. The resulting product is separated by vacuum filtration, and the filtrate is discarded. The filtered precipitate is washed with deionized water 3 times, each time with an amount of 115 mL to remove residual impurities and unreacted silver ions, and then washed once with anhydrous ethanol, each time with an amount of 65 mL to promote drying. The washed precipitate is transferred to a vacuum drying oven and dried at 66°C for 9.2 hours to obtain a dry silver-doped titanium dioxide precursor powder. The dried precursor powder is placed in a high-temperature tube furnace, heated to 480°C at a heating rate of 3.6°C / min, and kept in an air atmosphere for 2.6 hours. After sintering, it is naturally cooled to room temperature, and the doped titanium dioxide particles are obtained after grinding and dispersion.

[0048] The average diameter of the silica-loaded doped titanium dioxide particles of this example is 159 nm.

[0049] The heat stabilizer in this embodiment is benzotriazole.

[0050] The curing agent in this embodiment is di-tert-butyl peroxide.

[0051] A method for preparing an antibacterial material for cookware according to this embodiment includes the following steps: S1. Place the surface-modified boron nitride nanotubes coated with silver filler and silica-loaded doped titanium dioxide particles and polyethylene glycol in a 500 mL beaker, add half of the ethanol, place the beaker on a magnetic stirrer, and stir at a stirring rate of 560 rpm for 39 minutes until a uniform nanomaterial dispersion is formed, add polytetrafluoroethylene powder, silicone resin and thermal stabilizer to the above nanomaterial dispersion, continue stirring at a rate of 460 rpm, and gradually add the remaining half of the ethanol for 69 minutes to ensure that the polytetrafluoroethylene and silicone resin are fully mixed and evenly dispersed to obtain a uniform mixed solution.

[0052] S2. Heat the uniform mixed liquid obtained in step S1 to 53°C, increase the temperature at a heating rate of 2.9°C / min, and maintain constant temperature stirring for 69 minutes to promote solvent volatilization and form a high-viscosity coating slurry. After the slurry is formed, slowly add the curing agent and continue stirring at a stirring rate of 460rpm for 39 minutes to ensure that the curing agent and the slurry are fully mixed.

[0053] S3. The obtained slurry is coated on the surface of the clean and dry cookware substrate by spraying, and the coating thickness is controlled at 29μm. After coating, the cookware is placed in an oven at 66℃ and kept warm for 39 minutes to preliminarily dry the coating. The cookware is then transferred to a high-temperature oven and heated to 265℃ at a heating rate of 6.5℃ / min and kept warm for 2.6 hours to complete the curing and adhesion process of the coating. The cured cookware is naturally cooled to room temperature to finally obtain an antibacterial cookware material.

[0054] Example 3

[0055] An antibacterial material for cookware and a preparation method thereof, comprising the following components, measured by weight: 1.1 parts of surface-modified boron nitride nanotube-coated silver filler, 6 parts of doped titanium dioxide particles loaded with silicon dioxide, 31 parts of polytetrafluoroethylene, 13 parts of silicone resin, 2.2 parts of a thermal stabilizer, 0.8 parts of polyethylene glycol 400, 51 parts of ethanol, and 2.2 parts of a curing agent.

[0056] The preparation method of the surface modified boron nitride tube coated silver filler of this embodiment is as follows: by weight, 15 parts of boron nitride tube coated silver filler are added to 130 parts of anhydrous ethanol, stirred at a stirring rate of 620 rpm for 36 minutes, and ultrasonic treatment is performed after the stirring is completed to obtain a suspension, wherein the parameters of the ultrasonic treatment are: sound power of 260 W, frequency of 46 kHz, and ultrasonic time of 26 minutes, and then 1.9 parts of KH-550 are continued to be added, and then at a temperature of 72°C, stirring is continued at a stirring rate of 420 rpm for 26 minutes. After the stirring is completed, the reaction solution is separated by vacuum filtration, and the filter residue is collected. The filter residue is transferred to a beaker and washed with 130 mL of anhydrous ethanol for 3 times, each stirring time is 8 minutes to remove unreacted KH-550 and impurities. After the washing is completed, the filter residue is filtered and placed in a vacuum drying oven, and dried at 66°C for 11 hours to obtain a surface modified boron nitride tube coated silver filler.

[0057] The preparation method of the boron nitride tube coated silver filler of the present embodiment is as follows: 3.9 parts of boron nitride nanotubes are weighed in parts by weight and placed in a 250 mL beaker, 130 mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, stirred at a stirring rate of 620 rpm for 26 minutes, then the beaker is placed in an ultrasonic cleaner, ultrasonically treated for 26 minutes under the conditions of an ultrasonic power of 260 W and a frequency of 46 kHz to form a boron nitride nanotube suspension, 1.3 parts of silver nitrate are weighed and dissolved in 130 mL of deionized water to obtain a silver nitrate solution, the boron nitride nanotube suspension is added to the silver nitrate solution, the mixture is placed on a magnetic stirrer, stirred at a stirring rate of 620 rpm for 36 minutes, the mixed solution is transferred to a vacuum ultrasonic device, and heated at -0.092 MPa under vacuum pressure conditions, the ultrasonic treatment was carried out with an ultrasonic power of 260 W, a frequency of 46 kHz, and a treatment time of 26 min. After the vacuum ultrasonic treatment, the mixture was restored to normal pressure, and the mixed solution was heated to 56 ° C. Then, 0.1 mol / L glucose solution was slowly added dropwise at a rate of 1.6 mL / min. The total volume was controlled at 26 mL. Constant temperature stirring was continued for 78 min until the color of the solution gradually changed from colorless to light gray. The reaction solution was cooled and separated by vacuum filtration. The filter residue was collected and washed twice with deionized water, each time with an amount of 130 mL. Subsequently, it was washed once with anhydrous ethanol, each time with an amount of 80 mL. The washed filter residue was transferred to a vacuum drying oven and dried at 66 ° C for 11 h to obtain a boron nitride tube coated with silver filler.

[0058] The preparation method of the boron nitride tube of the present embodiment is as follows: 6.8 parts of amorphous boron powder are weighed by weight and placed in a graphite crucible of a high-temperature inert atmosphere tube furnace, the inside of the tube furnace is evacuated to vacuum, the vacuum degree is controlled at -0.092MPa, and then argon gas is introduced for protection, the flow rate is controlled at 260mL / min, the furnace temperature is heated to 980°C at a heating rate of 8°C / min, and the temperature is kept for 48min, and the boron powder is activated. After the activation treatment is completed, the furnace temperature is continued to be heated to 1320°C at a heating rate of 16°C / min, and 320mL / min of ammonia is introduced for nitridation reaction at the same time, and the insulation time is 3.2h. After the reaction is completed, the ammonia is stopped, and 260mL / min of argon is introduced for protection, and the furnace temperature is reduced to room temperature at a cooling rate of 8°C / min to obtain a preliminarily generated boron nitride product, and the preliminarily generated product is taken out and placed in a beaker, and 130mL 0.34 mol / L dilute hydrochloric acid solution was placed on a magnetic stirrer and stirred at a stirring rate of 420 rpm for 48 min to carry out acid washing on the product. The product after acid washing was washed with deionized water for 4 times, each time with an amount of 130 mL, until the pH of the washing solution was close to neutral, and then washed with anhydrous ethanol once, each time with an amount of 80 mL, to complete further washing. The washed product was transferred to a vacuum drying oven and dried at 72 ° C for 19.2 h to obtain dry boron nitride nanotubes.

[0059] The surface-modified boron nitride tube coated with silver filler in this embodiment has an average diameter of 49 nm and an average length of 1030 nm.

[0060] The preparation method of the silica-loaded doped titanium dioxide particles of the present embodiment is as follows: by weight, 6.2 parts of doped titanium dioxide particles are weighed and placed in a 250 mL beaker, 130 mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 420 rpm for 36 min until a uniform dispersion is formed, 4.2 parts of tetraethyl orthosilicate are weighed and slowly added to the above dispersion, the dropping rate is controlled to 1.6 mL / min, and the stirring rate is maintained at 520 rpm, and stirring is continued for 48 min until the tetraethyl orthosilicate is completely mixed, 0.1 mol / L hydrochloric acid solution is slowly added to the resulting mixed solution, the dropping rate is controlled to 0.8 mL / min, and the stirring rate is maintained at 420 rpm, the pH of the solution is adjusted to 3.2, and stirring is continued for 48 min to complete the hydrolysis process of the tetraethyl orthosilicate, The obtained solution was transferred to a water bath at 86°C, heated and kept at a constant temperature for 78 minutes to promote the deposition of silica on the surface of the doped titanium dioxide particles. After the reaction was completed, the reaction solution was naturally cooled to room temperature, and the obtained precipitate was separated by vacuum filtration, and the filtrate was discarded. The precipitate was washed with deionized water 4 times, each time with an amount of 130 mL, to remove unreacted impurities and by-products, and then washed once with anhydrous ethanol, each time with an amount of 80 mL. The washed precipitate was transferred to a vacuum drying oven and dried at 72°C for 10.4 hours to obtain dry silica-loaded doped titanium dioxide particles. The dried sample was placed in a tubular furnace, heated to 460°C at a heating rate of 4.2°C / min, and kept warm in an air atmosphere for 3.2 hours. After completing the sintering treatment of the material, silica-loaded doped titanium dioxide particles were obtained.

[0061] The preparation method of the doped titanium dioxide particles of this embodiment is as follows: 13 parts of tetrabutyl titanate are weighed by weight and placed in a 250mL beaker, 80mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 520rpm for 36min until a uniform tetrabutyl titanate solution is formed; 1.4 parts of silver nitrate are weighed and dissolved in 38mL of deionized water to obtain a silver nitrate solution; the silver nitrate solution is slowly added dropwise to the tetrabutyl titanate solution at a dropping rate of 1.6mL / min, while the stirring rate is maintained at 620rpm, and stirring is continued for 48min to ensure that the silver ions are uniformly dispersed in the tetrabutyl titanate solution, and 0.1mol / L of hydrochloric acid solution is slowly added dropwise to the above-mentioned mixed solution at a dropping rate of 1.6mL / min, and the stirring rate is maintained at 520rpm, and the pH of the solution is adjusted to 2.2 to promote the hydrolysis reaction of tetrabutyl titanate After the addition is completed, the resulting solution is transferred to a reactor and heated and kept at 92°C for 9.6 hours to complete the formation of titanate gel and the silver ion doping process. After the reaction is completed, the reactor is naturally cooled to room temperature, and the resulting product is separated by vacuum filtration, and the filtrate is discarded. The filtered precipitate is washed with deionized water 4 times, each time with an amount of 130 mL to remove residual impurities and unreacted silver ions, and then washed once with anhydrous ethanol, each time with an amount of 80 mL to promote drying. The washed precipitate is transferred to a vacuum drying oven and dried at 72°C for 10.4 hours to obtain a dry silver-doped titanium dioxide precursor powder. The dried precursor powder is placed in a high-temperature tube furnace, heated to 510°C at a heating rate of 4.2°C / min, and kept in an air atmosphere for 3.2 hours. After sintering is completed, it is naturally cooled to room temperature, and doped titanium dioxide particles are obtained after grinding and dispersion.

[0062] The average diameter of the silica-loaded doped titanium dioxide particles of this example is 198 nm.

[0063] The heat stabilizer in this embodiment is Irganox 1010.

[0064] The curing agent in this embodiment is triethylenetetramine.

[0065] A method for preparing an antibacterial material for cookware according to this embodiment includes the following steps: S1. Place the surface-modified boron nitride nanotubes coated with silver filler and silica-loaded doped titanium dioxide particles and polyethylene glycol in a 500 mL beaker, add half of ethanol, place the beaker on a magnetic stirrer, and stir at a stirring rate of 620 rpm for 48 minutes until a uniform nanomaterial dispersion is formed, add polytetrafluoroethylene powder, silicone resin and thermal stabilizer to the above nanomaterial dispersion, continue stirring at a rate of 520 rpm, and gradually add the remaining half of ethanol for 78 minutes to ensure that the polytetrafluoroethylene and silicone resin are fully mixed and evenly dispersed to obtain a uniform mixed solution.

[0066] S2. Heat the uniform mixed liquid obtained in step S1 to 56°C, increase the temperature at a heating rate of 3.8°C / min, and maintain constant temperature stirring for 78 minutes to promote solvent volatilization and form a high-viscosity coating slurry. After the slurry is formed, slowly add the curing agent and continue stirring at a stirring rate of 520rpm for 48 minutes to ensure that the curing agent and the slurry are fully mixed.

[0067] S3. The obtained slurry is coated on the surface of the clean and dry cookware substrate by scraping. The coating thickness is controlled at 38μm. After coating, the cookware is placed in an oven at 72℃ and kept warm for 48 minutes to preliminarily dry the coating. The cookware is then transferred to a high-temperature oven and heated to 280℃ at a heating rate of 8℃ / min and kept warm for 3.2 hours to complete the curing and adhesion process of the coating. The cured cookware is naturally cooled to room temperature to finally obtain an antibacterial material for cookware.

[0068] Example 4

[0069] An antibacterial material for cookware and a preparation method thereof, comprising the following components, measured by weight: 1.5 parts of surface-modified boron nitride nanotube-coated silver filler, 8 parts of doped titanium dioxide particles loaded with silicon dioxide, 35 parts of polytetrafluoroethylene, 15 parts of silicone resin, 3.0 parts of thermal stabilizer, 1 part of polyethylene glycol 400, 55 parts of ethanol, and 3 parts of curing agent.

[0070] The preparation method of the surface modified boron nitride tube coated silver filler of this embodiment is as follows: by weight, 18 parts of boron nitride tube coated silver filler are added to 150 parts of anhydrous ethanol, stirred at a stirring rate of 700 rpm for 40 minutes, and after the stirring is completed, ultrasonic treatment is performed to obtain a suspension, wherein the parameters of the ultrasonic treatment are: sound power of 300 W, frequency of 50 kHz, and ultrasonic time of 30 minutes, then 2.5 parts of KH-550 are continued to be added, and then at a temperature of 80°C, stirring is continued at a stirring rate of 500 rpm for 30 minutes. After the stirring is completed, the reaction solution is separated by vacuum filtration, and the filter residue is collected. The filter residue is transferred to a beaker and washed 4 times with 150 mL of anhydrous ethanol, each stirring time is 10 minutes to remove unreacted KH-550 and impurities. After the washing is completed, the filter residue is filtered and placed in a vacuum drying oven, and dried at 70°C for 12 hours to obtain a surface modified boron nitride tube coated silver filler.

[0071] The preparation method of the boron nitride tube coated silver filler of the present embodiment is as follows: 4.5 parts of boron nitride nanotubes are weighed by weight and placed in a 250 mL beaker, 150 mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 700 rpm for 30 minutes, then the beaker is placed in an ultrasonic cleaner, and ultrasonic treatment is performed for 30 minutes under the conditions of an ultrasonic power of 300 W and a frequency of 50 kHz to form a boron nitride nanotube suspension, 1.5 parts of silver nitrate are weighed and dissolved in 150 mL of deionized water to obtain a silver nitrate solution, the boron nitride nanotube suspension is added to the silver nitrate solution, the mixture is placed on a magnetic stirrer, and stirred at a stirring rate of 700 rpm for 40 minutes, the mixed solution is transferred to a vacuum ultrasonic device, and the mixture is heated at -0.1 MPa under vacuum pressure conditions, the ultrasonic treatment was carried out with an ultrasonic power of 300 W, a frequency of 50 kHz, and a treatment time of 30 min. After the vacuum ultrasonic treatment, the mixture was restored to normal pressure, and the mixed solution was heated to 60°C, and then 0.1 mol / L glucose solution was slowly added dropwise at a rate of 2 mL / min. The total volume was controlled at 30 mL, and constant temperature stirring was continued for 90 min until the color of the solution gradually changed from colorless to light gray. The reaction solution was cooled and separated by vacuum filtration, the filter residue was collected, and washed with deionized water for 3 times, each time with an amount of 150 mL, and then washed with anhydrous ethanol for 2 times, each time with an amount of 100 mL. The washed filter residue was transferred to a vacuum drying oven and dried at 70°C for 12 h to obtain a boron nitride tube coated with silver filler.

[0072] The preparation method of the boron nitride tube of the present embodiment is as follows: 8.0 parts of amorphous boron powder are weighed by weight and placed in a graphite crucible of a high-temperature inert atmosphere tube furnace, the inside of the tube furnace is evacuated to vacuum, the vacuum degree is controlled at -0.1MPa, and then argon gas is introduced for protection, the flow rate is controlled at 300mL / min, the furnace temperature is heated to 1100°C at a heating rate of 10°C / min, and the temperature is kept for 60min to activate the boron powder. After the activation treatment is completed, the furnace temperature is continued to be heated to 1400°C at a heating rate of 20°C / min, and 400mL / min of ammonia is introduced for nitridation reaction at the same time, and the insulation time is 4h. After the reaction is completed, the ammonia introduction is stopped, and 300mL / min of argon gas is introduced for protection, and the furnace temperature is reduced to room temperature at a cooling rate of 10°C / min to obtain a preliminarily generated boron nitride product. The preliminarily generated product is taken out and placed in a beaker, and 150mL 0.5 mol / L dilute hydrochloric acid solution was placed on a magnetic stirrer and stirred at a stirring rate of 500 rpm for 60 min to carry out acid washing on the product. The product after acid washing was washed with deionized water for 5 times, each time with an amount of 150 mL, until the pH of the washing solution was close to neutral, and then washed with anhydrous ethanol for 2 times, each time with an amount of 100 mL, to complete further washing. The washed product was transferred to a vacuum drying oven and dried at 80 ° C for 24 h to obtain dry boron nitride nanotubes.

[0073] The surface-modified boron nitride tube coated with silver filler in this embodiment has an average diameter of 65 nm and an average length of 1350 nm.

[0074] The preparation method of the silica-loaded doped titanium dioxide particles of this embodiment is as follows: by weight, 7.0 parts of doped titanium dioxide particles are weighed and placed in a 250 mL beaker, 150 mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 500 rpm for 40 min until a uniform dispersion is formed, 5.0 parts of tetraethyl orthosilicate are weighed and slowly added to the above dispersion, the dropping rate is controlled to 2.0 mL / min, and the stirring rate is maintained at 600 rpm, and stirring is continued for 60 min until the tetraethyl orthosilicate is completely mixed, 0.1 mol / L hydrochloric acid solution is slowly added to the resulting mixed solution, the dropping rate is 1.0 mL / min, and the stirring rate is maintained at 500 rpm, the pH of the solution is adjusted to 4.0, and stirring is continued for 60 min to complete the hydrolysis of the tetraethyl orthosilicate Process, the resulting solution is transferred to a 90°C water bath, heated and kept at a constant temperature for 90 minutes to promote the deposition of silica on the surface of the doped titanium dioxide particles. After the reaction is completed, the reaction solution is naturally cooled to room temperature, and the resulting precipitate is separated by vacuum filtration, the filtrate is discarded, and the precipitate is washed with deionized water 5 times, each time with an amount of 150 mL, to remove unreacted impurities and by-products, and then washed with anhydrous ethanol 2 times, each time with an amount of 100 mL. The washed precipitate is transferred to a vacuum drying oven and dried at 80°C for 12 hours to obtain dry silica-loaded doped titanium dioxide particles. The dried sample is placed in a tubular furnace, heated to 500°C at a heating rate of 5°C / min, and kept warm in an air atmosphere for 4 hours. After completing the sintering treatment of the material, silica-loaded doped titanium dioxide particles are obtained.

[0075] The preparation method of the doped titanium dioxide particles of this embodiment is as follows: 15 parts of tetrabutyl titanate are weighed by weight and placed in a 250mL beaker, 100mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 600rpm for 40min until a uniform tetrabutyl titanate solution is formed; 1.8 parts of silver nitrate are weighed and dissolved in 45mL of deionized water to obtain a silver nitrate solution; the silver nitrate solution is slowly added dropwise to the tetrabutyl titanate solution at a dropping rate of 2.0mL / min, while the stirring rate is maintained at 700rpm, and stirring is continued for 60min to ensure that the silver ions are uniformly dispersed in the tetrabutyl titanate solution, 0.1mol / L of hydrochloric acid solution is slowly added dropwise to the above-mentioned mixed solution at a dropping rate of 2.0mL / min, and the stirring rate is maintained at 600rpm, and the pH of the solution is adjusted to 3.0 to promote the hydrolysis of tetrabutyl titanate. After the addition is completed, the resulting solution is transferred to a reactor and heated at 95°C for 12 hours to complete the formation of titanate gel and the silver ion doping process. After the reaction is completed, the reactor is naturally cooled to room temperature. The resulting product is separated by vacuum filtration, and the filtrate is discarded. The filtered precipitate is washed with deionized water 5 times, each time with an amount of 150 mL to remove residual impurities and unreacted silver ions, and then washed with anhydrous ethanol twice, each time with an amount of 100 mL to promote drying. The washed precipitate is transferred to a vacuum drying oven and dried at 80°C for 12 hours to obtain a dry silver-doped titanium dioxide precursor powder. The dried precursor powder is placed in a high-temperature tube furnace, heated to 550°C at a heating rate of 5°C / min, and kept in an air atmosphere for 4 hours. After sintering, it is naturally cooled to room temperature, and doped titanium dioxide particles are obtained after grinding and dispersion.

[0076] The average diameter of the silica-loaded doped titanium dioxide particles of this example is 260 nm.

[0077] The heat stabilizer in this embodiment is Irganox 1010 or benzotriazole.

[0078] The curing agent in this embodiment is triethylenetetramine or di-tert-butyl peroxide.

[0079] A method for preparing an antibacterial material for cookware according to this embodiment includes the following steps: S1. Place the surface-modified boron nitride nanotubes coated with silver filler and silica-loaded doped titanium dioxide particles and polyethylene glycol in a 500mL beaker, add half of ethanol, place the beaker on a magnetic stirrer, and stir at a stirring rate of 700rpm for 60min until a uniform nanomaterial dispersion is formed, add polytetrafluoroethylene powder, silicone resin and thermal stabilizer to the above nanomaterial dispersion, continue stirring at a rate of 600rpm, and gradually add the remaining other half of ethanol for 90min to ensure that the polytetrafluoroethylene and silicone resin are fully mixed and evenly dispersed to obtain a uniform mixed solution.

[0080] S2. Heat the uniform mixed liquid obtained in step S1 to 60°C, increase the temperature at a heating rate of 5°C / min, and maintain constant temperature stirring for 90 minutes to promote solvent volatilization and form a high-viscosity coating slurry. After the slurry is formed, slowly add the curing agent and continue stirring at a stirring rate of 600 rpm for 60 minutes to ensure that the curing agent and the slurry are fully mixed.

[0081] S3. Apply the obtained slurry on the surface of the clean and dry cookware substrate by spraying or scraping. The coating thickness is controlled at 50μm. After coating, place the cookware in an oven at 80℃ and keep it warm for 60 minutes to preliminarily dry the coating. Then transfer the cookware to a high-temperature oven, heat it to 300℃ at a heating rate of 10℃ / min, and keep it warm for 4 hours to complete the curing and adhesion process of the coating. After curing, naturally cool the cookware to room temperature to finally obtain an antibacterial material for cookware.

[0082] Comparative Example 1 The method is basically the same as Example 1, except that the boron nitride nanotube-coated silver filler is not subjected to surface modification treatment.

[0083] Comparative Example 2 The method is basically the same as Example 1, except that the boron nitride nanotubes are not coated with silver, but the surface modification treatment is directly performed on the boron nitride nanotubes.

[0084] Comparative Example 3 The method is basically the same as Example 1, except that the surface-modified boron nitride nanotube-coated silver filler is not added to the cookware material.

[0085] Comparative Example 4 The method is basically the same as Example 1, except that the doped titanium dioxide particles are not loaded with silicon dioxide.

[0086] Comparative Example 5 The method is basically the same as Example 1, except that no silver nitrate is added in the preparation of doped titanium dioxide particles, so the titanium dioxide particles are not doped with silver, but the surface of the titanium dioxide particles is still loaded with silicon dioxide.

[0087] Comparative Example 6 The method is basically the same as Example 1, except that no doped titanium dioxide particles loaded with silicon dioxide are added when preparing the cookware material.

[0088] Performance Test: Wear resistance: A universal friction and wear tester (MFT-5000) was used to evaluate the wear resistance of the cookware material, with the friction coefficient and wear rate as the core evaluation criteria. During the test, a reciprocating linear motion mode was used, and the test parameters were set to a loading force of 10 N, a frequency of 1 Hz, and a test duration of 10 minutes. Silicon nitride ceramic balls with a diameter of 9.525 mm were used as the grinding material. After the test, the wear marks produced on the coating surface were observed using an MFP-D three-dimensional topography instrument, the morphological characteristics of the wear marks were analyzed, and the wear amount was calculated. Finally, the wear rate W was obtained to comprehensively measure the performance of the cookware material in terms of wear resistance.

[0089] In order to comprehensively evaluate the antibacterial properties of the wear-resistant materials of cookware, the test is divided into two parts: quantitative analysis and qualitative analysis. The experimental object is a sample film prepared from the cookware material. The sample film is cut from the surface of the cookware material in equal proportions, or is prepared by processing the cookware material to ensure that the test results can accurately reflect the antibacterial properties of the material. In the quantitative analysis, Escherichia coli and Staphylococcus aureus were selected as test strains. Before the experiment, liquid and solid culture media were prepared, and the experimental equipment and test sample films were sterilized at high temperature and high pressure to ensure a sterile environment. Subsequently, the strain was activated and a concentration of 2.5×10 5 CFU / mL of bacterial suspension, and adjust the bacterial suspension concentration by ten-fold dilution method and inoculate it into liquid culture medium, add test sample membrane at the same time, and culture under appropriate conditions for 8-10 hours. Then, take 100 μL of bacterial suspension for gradient dilution to 10 - 4 CFU / mL concentration range, and the diluted bacterial solution was spread on the surface of the agar medium, cultured at 37°C for 24 hours, the colony growth was observed and the number of colonies was counted, and the antibacterial performance of the material was quantified by calculating the total number of colonies in the inoculated bacterial solution. In the qualitative analysis, after the same preliminary experimental preparation as the quantitative analysis, the diluted bacterial solution was evenly spread on the surface of the solid culture medium, and a sample film of the pot material with a diameter of 2 cm was placed on the surface of the coated culture medium. After culturing at 37°C for 24 hours, the size of the inhibition zone around the sample film was observed, and the antibacterial ability of the material was evaluated by the diameter of the inhibition zone. Finally, the inhibition rate was calculated by counting the total number of colonies in the inoculated bacterial solution, and the antibacterial performance of the pot material was characterized by the formula inhibition rate (%) = [(total number of colonies in the control group - total number of colonies in the sample group) / total number of colonies in the control group] × 100%. This test method combines quantitative and qualitative analysis, which can comprehensively and systematically characterize the antibacterial performance of the pot material and provide a scientific basis for the practical application of the material.

[0090] The properties of the cookware materials of Examples 1 to 4 and Comparative Examples 1 to 6 are summarized in Table 1.

[0091] Table 1 Performance of cookware materials of Examples 1 to 4 and Comparative Examples 1 to 6

[0092] The main difference between Comparative Example 1 and Example 1 is that the boron nitride nanotube-coated silver filler is not subjected to surface modification. As can be seen from the table, the friction coefficient in Example 1 is lower (0.12) and the wear rate is lower (8.0 × 10 -5 mm 3 / N·m), while the friction coefficient (0.15) and wear rate (12.0 × 10 -5 mm 3 / N·m) increased significantly. This shows that surface modification of boron nitride nanotube-coated silver filler can significantly improve the wear resistance of the material. This is because the unmodified filler has poor dispersibility and is prone to aggregation during friction, resulting in increased friction coefficient and wear rate. In terms of antibacterial performance, the antibacterial rate of Example 1 is 98.5%, and the diameter of the antibacterial zone is 18.0 mm, while the antibacterial rate of Comparative Example 1 is only 95.0%, and the diameter of the antibacterial zone is 15.0 mm. This shows that the surface modification treatment not only improves the dispersibility of the filler, but also effectively enhances the release efficiency of silver ions, thereby improving the antibacterial ability of the material.

[0093] The main difference between Comparative Example 2 and Example 1 is that the boron nitride nanotubes are not coated with silver, but directly subjected to surface modification treatment. As can be seen from the table, the friction coefficient (0.13) and wear rate (8.5× 10 -5 mm 3 / N·m) is higher than that of Example 1. This shows that the silver-coated boron nitride nanotubes are more effective in improving the wear resistance. In terms of antibacterial performance, the antibacterial rate of Comparative Example 2 is 96.5%, and the diameter of the antibacterial zone is 16.5 mm, both lower than that of Example 1. This is because the antibacterial property of the uncoated silver boron nitride nanotubes mainly depends on the surface modification treatment, and lacks the broad-spectrum antibacterial effect of silver, resulting in a decrease in antibacterial performance.

[0094] The main difference between Comparative Example 3 and Example 1 is that the surface-modified boron nitride nanotube-coated silver filler is not added to the cookware material. As can be seen from the table, the friction coefficient (0.20) and wear rate (15.0 × 10 -5 mm 3 / N·m) is significantly higher than the friction coefficient (0.12) and wear rate (8.0 × 10 -5 mm 3 / N·m). This shows that surface-modified boron nitride nanotubes coated with silver fillers play a key role in improving wear resistance. This is because without the filler, the wear resistance of the material is significantly reduced, and large deformation and wear are easily generated during friction. In terms of antibacterial performance, the antibacterial rate of Comparative Example 3 is only 90.0%, and the diameter of the antibacterial zone is only 12.0 mm, which is much lower than that of Example 1. This shows that boron nitride nanotubes coated with silver fillers are crucial to improving antibacterial performance, because the broad-spectrum antibacterial effect of silver and the dispersibility of the filler work together to achieve a higher antibacterial effect.

[0095] The main difference between Comparative Example 4 and Example 1 is that the doped titanium dioxide particles are not loaded with silicon dioxide. As can be seen from the table, the friction coefficient (0.12) and wear rate (8.5 × 10 -5 mm 3 / N·m) is slightly higher than that of Example 1. This shows that the doped titanium dioxide particles loaded with silica have a certain improvement effect on the wear resistance. This is because the silica loading can further improve the dispersibility and reinforcing effect of the filler, thereby reducing the friction coefficient and wear rate. In terms of antibacterial performance, the antibacterial rate of Comparative Example 4 is 98.0%, and the antibacterial circle diameter is 17.0 mm, which is slightly lower than that of Example 1. This is because the doped titanium dioxide particles loaded with silica can provide additional antibacterial active sites, thereby enhancing the release efficiency of silver ions, and the antibacterial performance is slightly reduced when silica is not loaded.

[0096] The main difference between Comparative Example 5 and Example 1 is that no silver nitrate is added to the doped titanium dioxide particles, so the titanium dioxide particles are not doped with silver, but the surface of the titanium dioxide particles is still loaded with silicon dioxide. As can be seen from the table, the friction coefficient (0.13) and wear rate (9.0 × 10 -5 mm 3 / N·m) is slightly higher than that in Example 1. This shows that the silver-doped titanium dioxide particles contribute to the wear resistance to a certain extent, because silver doping can improve the mechanical strength and stability of the filler, while the effect of the particles loaded with only silicon dioxide is slightly weaker. In terms of antibacterial performance, the antibacterial rate of Comparative Example 5 is 97.5%, and the diameter of the antibacterial zone is 16.0 mm, which is lower than that in Example 1. This shows that silver doping plays an important role in improving the antibacterial performance, because silver ions can significantly enhance the antibacterial ability of the material, while the titanium dioxide particles not doped with silver only rely on the effect of silicon dioxide, resulting in a decrease in the antibacterial effect.

[0097] The main difference between Comparative Example 6 and Example 1 is that the cookware material does not contain doped titanium dioxide particles loaded with silicon dioxide. As can be seen from the table, the friction coefficient (0.25) and wear rate (18.0 × 10 -5 mm 3 / N·m) is significantly higher than that of Example 1. This shows that the doped titanium dioxide particles loaded with silica are crucial to improving the wear resistance. This is because without this filler, the material lacks a reinforcing effect during the friction process, and the wear increases significantly. In terms of antibacterial performance, the antibacterial rate of Comparative Example 6 is only 85.0%, and the diameter of the antibacterial zone is only 10.0 mm, which is much lower than that of Example 1. This is because after the doped titanium dioxide particles loaded with silica are not added, the material loses its main antibacterial active ingredients, resulting in a significant decrease in antibacterial performance.

[0098] In summary, the synergistic effect between components is the key to achieving excellent performance of cookware materials. The modified boron nitride nanotubes coated with silver filler improve the dispersion and interfacial bonding of the filler through surface modification, while the lubricating effect and antibacterial properties of silver significantly enhance the wear resistance and antibacterial properties of the material; the silver-doped titanium dioxide particles further improve their dispersion stability and antibacterial active sites through the loading of silica, thereby enhancing the overall antibacterial effect of the material; the silica loading not only improves the mechanical properties of the particles, but also plays an important auxiliary role in improving the antibacterial efficiency and wear resistance. These components not only significantly reduce the friction coefficient and wear rate through the synergistic effects of "strength enhancement", "lubrication and wear reduction" and "broad-spectrum antibacterial", but also achieve a significant increase in the antibacterial rate and the diameter of the antibacterial zone, ultimately giving the material excellent comprehensive performance. This shows that the rational design and optimization of the synergistic effect of multiple components is the core strategy to achieve high-performance cookware materials.

[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A cookware antibacterial material, characterized in that: The invention comprises the following components in parts by weight: 0.5-1.5 parts of surface modified boron nitride nanotube coated silver filler, 3-8 parts of doped titanium dioxide particles loaded with silicon dioxide, 25-35 parts of polytetrafluoroethylene, 10-15 parts of silicone resin, 1.0-3.0 parts of heat stabilizer, 0.5-1 parts of polyethylene glycol 400, 45-55 parts of ethanol and 1-3 parts of curing agent.

2. The antibacterial material for cookware according to claim 1, characterized in that: The preparation method of the surface modified boron nitride tube coated silver filler is as follows: by weight, 10 to 18 parts of boron nitride tube coated silver filler are added to 100 to 150 parts of anhydrous ethanol, stirred at a stirring rate of 500 to 700 rpm for 30 to 40 minutes, and after the stirring is completed, ultrasonic treatment is performed to obtain a suspension, wherein the parameters of the ultrasonic treatment are: sound power of 200 to 300 W, frequency of 40 to 50 kHz, and ultrasonic time of 20 to 30 minutes, and then 1.0 to 2.5 parts of KH-550 are continued to be added, and then at a temperature of 60 to 80 ° C, stirring is continued at a stirring rate of 300 to 500 rpm for 20 to 30 minutes. After the stirring is completed, the reaction solution is separated by vacuum filtration, the filter residue is collected, and the filter residue is transferred to a beaker, and 100 to 150 The mixture was washed with 50 mL of anhydrous ethanol for 3 to 4 times, with each stirring time of 5 to 10 min, to remove unreacted KH-550 and impurities. After washing, the residue was filtered and placed in a vacuum drying oven, and dried at 60 to 70 ° C for 10 to 12 h to obtain a surface-modified boron nitride tube coated with silver filler.

3. The antibacterial material for cookware according to claim 2, characterized in that: The preparation method of the boron nitride tube-coated silver filler is as follows: 3.0-4.5 parts of boron nitride nanotubes are weighed in parts by weight and placed in a 250 mL beaker, 100-150 mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 500-700 rpm for 20-30 minutes, then the beaker is placed in an ultrasonic cleaner, and ultrasonic treatment is performed for 20-30 minutes under the conditions of an ultrasonic power of 200-300 W and a frequency of 40-50 kHz to form a boron nitride nanotube suspension, 1.0-1.5 parts of silver nitrate are weighed and dissolved in 100-150 mL of deionized water to obtain a silver nitrate solution, the boron nitride nanotube suspension is added to the silver nitrate solution, and the beaker is placed on a magnetic stirrer and stirred at a stirring rate of 500-700 rpm for 30-40 min, transfer the mixed solution to a vacuum ultrasonic device, and perform ultrasonic treatment under a vacuum pressure of -0.08-0.1 MPa, with an ultrasonic power of 200-300 W, a frequency of 40-50 kHz, and a treatment time of 20-30 min. After the vacuum ultrasonic treatment, return to normal pressure, heat the mixed solution to 50-60 °C, and then slowly add 0.1 mol / L glucose solution at a drop rate of 1-2 mL / min. The total volume is controlled at 20-30 mL. Continue to maintain constant temperature stirring for 60-90 min until the color of the solution gradually changes from colorless to light gray. After the reaction solution is cooled, separate it by vacuum filtration, collect the filter residue, and wash it 2-3 times with deionized water, each time with 100-150 mL, and then wash it 1-2 times with anhydrous ethanol, each time with 50-100 mL, the washed filter residue was transferred to a vacuum drying oven and dried at 60-70 °C for 10-12 h to obtain a boron nitride tube coated with silver filler.

4. The antibacterial material for cookware according to claim 3, characterized in that: The preparation method of the boron nitride tube is as follows: 5.0-8.0 parts of amorphous boron powder are weighed by weight and placed in a graphite crucible of a high-temperature inert atmosphere tube furnace, the inside of the tube furnace is evacuated to vacuum, the vacuum degree is controlled at -0.08-0.1 MPa, and then argon is introduced for protection, the flow rate is controlled at 200-300 mL / min, the furnace temperature is heated to 800-1100°C at a heating rate of 5-10°C / min, and the temperature is kept for 30-60 min, the boron powder is activated, and after the activation treatment is completed, the furnace temperature is continued to be heated to 1200-1400°C at a heating rate of 10-20°C / min, and 200-400 mL / min of ammonia is introduced for nitridation reaction, and the insulation time is 2-4 hours. After the reaction is completed, the ammonia is stopped, and 200-300 mL / min of ammonia is introduced. mL / min of argon, the furnace temperature was lowered to room temperature at a cooling rate of 5~10℃ / min to obtain a preliminarily generated boron nitride product, the preliminarily generated product was taken out and placed in a beaker, 100~150 mL of 0.1~0.5 mol / L dilute hydrochloric acid solution was added, and the product was placed on a magnetic stirrer and stirred at a stirring rate of 300~500 rpm for 30~60 min, and the product was acid-washed, and the product after acid washing was washed with deionized water for 3~5 times, each time with an amount of 100~150 mL, until the pH of the washing solution was close to neutral, and then washed with anhydrous ethanol 1~2 times, each time with an amount of 50~100 mL, to complete further washing, and the washed product was transferred to a vacuum drying oven, and dried at 60~80℃ for 12~24h to obtain dry boron nitride nanotubes.

5. The antibacterial material for cookware according to claim 1 or 2, characterized in that: The average diameter of the surface modified boron nitride tube coated with silver filler is 15-65nm, and the average length is 550-1350nm.

6. The antibacterial material for cookware according to claim 1, characterized in that: The preparation method of the silica-loaded doped titanium dioxide particles is as follows: by weight, 5.0-7.0 parts of doped titanium dioxide particles are weighed and placed in a 250 mL beaker, 100-150 mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 300-500 rpm for 30-40 min until a uniform dispersion is formed, 3.0-5.0 parts of tetraethyl orthosilicate are weighed and slowly added to the above dispersion, the dropping rate is controlled to 1.0-2.0 mL / min, and the stirring rate is maintained at 400-600 rpm, and stirring is continued for 30-60 min until the tetraethyl orthosilicate is completely mixed, and 0.1 mol / L hydrochloric acid solution is slowly added to the resulting mixed solution, the dropping rate is 0.5-1.0 mL / min, and the stirring rate is maintained at 300-500 rpm. rpm, adjust the solution pH to 2.0-4.0, and continue stirring for 30-60 minutes to complete the hydrolysis process of ethyl orthosilicate, transfer the resulting solution to a water bath at 80-90°C, heat and maintain constant temperature stirring for 60-90 minutes to promote the deposition of silicon dioxide on the surface of doped titanium dioxide particles. After the reaction is completed, the reaction solution is naturally cooled to room temperature, the resulting precipitate is separated by vacuum filtration, the filtrate is discarded, and the precipitate is washed with deionized water 3-5 times, each time with an amount of 100-150 mL, to remove unreacted impurities and by-products, and then washed with anhydrous ethanol 1-2 times, each time with an amount of 50-100 mL, the washed precipitate is transferred to a vacuum drying oven and dried at 60-80°C for 8-12h to obtain dry silica-loaded doped titanium dioxide particles. The dried sample is placed in a tubular furnace and heated to 400-500°C at a heating rate of 3-5°C / min and kept warm in an air atmosphere for 2-4 hours. After the sintering treatment of the material is completed, silica-loaded doped titanium dioxide particles are obtained.

7. The antibacterial material for cookware according to claim 6, characterized in that: The preparation method of the doped titanium dioxide particles is as follows: 10.0-15.0 parts of tetrabutyl titanate are weighed by weight and placed in a 250 mL beaker, 50-100 mL of anhydrous ethanol is added, the beaker is placed on a magnetic stirrer, and stirred at a stirring rate of 400-600 rpm for 30-40 minutes until a uniform tetrabutyl titanate solution is formed; 0.5-2.0 parts of silver nitrate are weighed and dissolved in 20-50 mL of deionized water to obtain a silver nitrate solution; the silver nitrate solution is slowly dripped into the tetrabutyl titanate solution at a dripping rate of 1.0-2.0 mL / min, while the stirring rate is maintained at 500-700 rpm, and the stirring is continued for 30-60 minutes to ensure that the silver ions are uniformly dispersed in the tetrabutyl titanate solution, and 0.1 mol / L of hydrochloric acid solution is slowly dripped into the above-mentioned mixed solution at a dripping rate of 1.0-2.0 mL / min, and the stirring rate is maintained at 400-600 rpm. rpm, adjust the solution pH to 1.0-3.0 to promote the hydrolysis reaction of tetrabutyl titanate. After the dropwise addition is completed, the resulting solution is transferred to a reactor and heated at 80-100°C for 6-12 hours to complete the formation of titanate gel and the silver ion doping process. After the reaction is completed, the reactor is naturally cooled to room temperature. The resulting product is separated by vacuum filtration, and the filtrate is discarded. The filtered precipitate is washed with deionized water for 3-5 times, each time with an amount of 100-150 mL to remove residual impurities and unreacted silver ions, and then washed with anhydrous ethanol 1-2 times, each time with an amount of 50-100 mL to promote drying. The washed precipitate is transferred to a vacuum drying oven and dried at 60-80°C for 8-12 hours to obtain a dry silver-doped titanium dioxide precursor powder. The dried precursor powder is placed in a high-temperature tube furnace, heated to 450~550℃ at a heating rate of 3~5℃ / min, and kept warm in an air atmosphere for 2~4h. After sintering, it is naturally cooled to room temperature, and doped titanium dioxide particles are obtained after grinding and dispersion.

8. The antibacterial material for cookware according to claim 1 or 6, characterized in that: The average diameter of the silicon dioxide-loaded doped titanium dioxide particles is 120-250 nm.

9. The antibacterial material for cookware according to claim 1, characterized in that: The thermal stabilizer is Irganox1010 or benzotriazole; The curing agent is triethylenetetramine or di-tert-butyl peroxide.

10. The method for preparing an antibacterial material for cookware according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Place the surface-modified boron nitride nanotubes coated with silver fillers and the silica-loaded doped titanium dioxide particles and polyethylene glycol in a 500 mL beaker, add half of the ethanol, place the beaker on a magnetic stirrer, and stir at a stirring rate of 500-700 rpm for 30-60 min until a uniform nanomaterial dispersion is formed, add polytetrafluoroethylene powder, silicone resin and thermal stabilizer to the above nanomaterial dispersion, continue stirring at a rate of 400-600 rpm, gradually add the remaining half of the ethanol, and stir for 60-90 min to ensure that the polytetrafluoroethylene and silicone resin are fully mixed and evenly dispersed to obtain a uniform mixed solution; S2. The uniform mixed solution obtained in step S1 is heated to 50-60°C at a heating rate of 2-5°C / min, and the mixture is stirred at a constant temperature for 60-90 min to promote the volatilization of the solvent and form a high-viscosity coating slurry. After the slurry is formed, the curing agent is slowly added, and the stirring is continued for 30-60 min at a stirring rate of 400-600 rpm to ensure that the curing agent and the slurry are fully mixed; S3. Apply the obtained slurry on the clean and dry surface of the cookware substrate by spraying or scraping. The coating thickness is controlled at 20~50μm. After coating, place the cookware in an oven at 60~80℃ and keep it warm for 30~60min to preliminarily dry the coating. Then transfer the cookware to a high-temperature oven and heat it to 250~300℃ at a heating rate of 5~10℃ / min and keep it warm for 2~4h to complete the curing and adhesion process of the coating. After curing, naturally cool the cookware to room temperature to finally obtain an antibacterial material for cookware.

Citation Information

Patent Citations

  • A non-stick cookware with a ceramic wear-resistant coating and its manufacturing process

    CN107080468B

  • Antibacterial non-stick cookware and manufacturing method thereof

    CN107981702B

  • Composition for non-stick paints and preparation method thereof

    CN101842445A

  • Cooker and manufacturing method of cooker

    CN107019407A

  • Polypropylene composite for logistic transportation packaging and preparation method of polypropylene composite

    CN107383602A

Cited By

  • Preparation process of PET (Polyethylene Terephthalate) film laser printing coating

    CN120173462A